Stable or fluctuating temperatures in winter: which is worse for your lungs? - Lam, K (BMJ Publishing Group, 2018)
The ratification of the Paris Agreement in 2015(1) signifies a worldwide consensus on climate change has been reached. The Intergovernmental Panel on Climate Change has warned as global warming intensifies, extreme weather events (such as heat waves, droughts, floods) will become more frequent and more severe(2). Indeed in the UK, within the first few months of 2018, there have already been a cold wave between late February and early March (with maximum temperature 8-12 oC below average for the time of year)(3) and an unusually warm week in April (which saw an rise of almost 20 oC from 6-7 oC in the previous week)(4). That heat waves or cold spells could lead to excess deaths have been documented in previous studies(5-7) and is probably unquestionable. However, even in the absence of extreme temperature episodes, exposure to so-called non-optimum ambient temperatures has shown to be associated with elevated risks of morbidity and mortality(8-10). A recent study of over 74 million deaths from 13 countries has found most of temperature-related short-term (days to weeks after the exposure) mortality displacement could in fact be attributed to moderate hot and cold temperatures, rather than extreme heat (temperature higher than 97.5th percentile) or cold (lower than 2.5th percentile)(9). Many of these previous studies have used mean daily temperature as the exposure metric. The fact that health impact has been observed in both colder and hotter temperatures suggests there is adaptation to usual temperatures and unexpected fluctuations in temperature may be more relevant. Temperature variability, as it is known, can be measured in different ways but mostly focusing on intraday (diurnal temperature range) or interday (change between neighbouring days) variability(11-13). Effects of longer term temperature variability, usually defined as standard deviation of the daily mean temperatures in summer and/or winter, have also been examined in the US population with significant associations with mortality observed(14-16)